Prediction of significant factors in the production of ethanol by ragi tapai co-culture using taguchi methodology - Azmi, Azlin Suhaida; Ngoh, Cheng Geik; Mel, Maizirwan (2011)
Ethanol production by co-culture of ragi tapai and Saccharomyces cerevisiae from unhydrolyzed cassava starch without addition of enzymes was conducted in a 2 liters batch fermentor. Taguchi’s method with orthogonal array of L8 was applied in design of experiment (DOE) and the results were analyzed using MINITAB v14 software. Seven factors; nitrogen-phosphorus-potassium (NPK), urea, fermentation temperature, ragi tapai concentration, S. cerevisiae concentration, agitation and co-culturing time were varied at two levels for each factor. The significant factors for the production of ethanol were determined by setting S/N ratio to ―larger-is-better for high yield ethanol and ―smaller-is-better for low yield of ethanol byproducts. The optimum values obtained for each factor were in agreement with each other. Both have optimum factors of; urea at 0.8 w/w%, dry ragi tapai and S. cerevisiae concentrations each at 10 w/w%, co-culturing time at 3 h gap, NPK at 0.09 w/w% and agitation speed at 100 rpm. The fermentation temperature for high ethanol yield where ―larger-is-better‖ favors 35oC whereas for the byproducts it favors 30oC. From the validation experiment conducted at 30oC in 10 liters fermentor, the ethanol concentration obtained was 68.00 g/L while all byproducts concentrations were below 9.00 g/L at the end of fermentation.